2000
DOI: 10.1258/1357633001935112
|View full text |Cite
|
Sign up to set email alerts
|

Patient cost-benefits of realtime teledermatology-a comparison of data from Northern Ireland and New Zealand

Abstract: As part of a randomized controlled trial of the costs and benefits of realtime teledermatology in comparison with conventional face-to-face appointments, patients were asked to complete a questionnaire at the end of their consultation. One hundred and nine patients took part in an initial teledermatology consultation and 94 in a face-to-face consultation. The proportion of patients followed up by the dermatologist was almost the same after teledermatology (24%) as after a hospital appointment (26%) and for sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 1 publication
0
54
0
Order By: Relevance
“…[3][4][5][6][7][8] Store-and-forward teledermatology using digital cameras has also recently been associated with reduced patient wait times, high patient satisfaction, [9][10][11][12][13] promising diagnostic reliability, [14][15][16][17] and clinical outcomes similar to conventional, faceto-face clinical care. 18,19 To date, however, the vast majority of teledermatology studies and projects have focused on industrialized nations, whereas the potential need for teledermatology may be most profound in the developing world.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Store-and-forward teledermatology using digital cameras has also recently been associated with reduced patient wait times, high patient satisfaction, [9][10][11][12][13] promising diagnostic reliability, [14][15][16][17] and clinical outcomes similar to conventional, faceto-face clinical care. 18,19 To date, however, the vast majority of teledermatology studies and projects have focused on industrialized nations, whereas the potential need for teledermatology may be most profound in the developing world.…”
mentioning
confidence: 99%
“…LI teledermatology can decrease total time necessary to complete a consultation visit from the patient's perspective. For example, researchers in New Zealand found that, compared to a clinic visit, the use of LI teledermatology saved patients an average of 3.45 hours of time, primarily due to reduced traveling time (Oakley et al, 2000). However, LI teledermatology does not necessarily reduce consult time for the dermatologist (Loane et al, 1999(Loane et al, , 2001bOakley et al, 2000).…”
Section: Clinical Outcomes For LI Teledermatologymentioning
confidence: 99%
“…In rural areas with large travelling distances telemedicine is considered to be a cost effective complement to conventional dermatological outpatient care [25,26]. A study in northern Norway shows that compared with the following three alternatives, (i) combination of patient travel to hospital and visiting service, (ii) patient travel to the nearest secondarycare centre and (iii) locally employed dermatologist, teledermatology was less costly of all [27].…”
Section: Telemedicinementioning
confidence: 99%